Pressure field in a tube with a general and arbitrary time- and position-dependent gas source - Degasperi, F. T.; Martins, M. N.; Takahashi, J.; Verardi, SLL (A V S Amer Inst Physics, 2004)
In this article we present analytical and numerical results for a pressure profile along the axis of a tube with a general and arbitrary time- and position-dependent gas source. The model is able to determine the pressure values along the tube, once the pumping speed at each extremity and the gas sources are specified. The time evolution of the pressure along a tube is presented for situations commonly found in high-vacuum applications, such as particle accelerators, colliders, storage rings, and synchrotron light sources. (C) 2004 American Vacuum Society.